Pristimerin‐induced uveal melanoma cell death via inhibiting PI3K/Akt/FoxO3a signalling pathway. Issue 11 (29th April 2020) - Yan, Fengxia; Liao, Rifang; Silva, Marta; Li, Shuai; Jiang, Yizhou; Peng, Tangming; Lazarovici, Philip; Zheng, Wenhua
Abstract: Uveal melanoma (UM) is a highly invasive intraocular malignancy with high mortality. Presently, there is no FDA‐approved standard for the treatment of metastatic UM. Pristimerin is a natural quinine methide triterpenoid compound with anti‐angiogenic, anti‐cancer and anti‐inflammatory activities. However, Pristimerin potential cytotoxic effect on UM was poorly investigated. In the present study, we found the migration and invasion of UM‐1 cells were inhibited by Pristimerin which also caused a rapid increase of ROS, decreased mitochondrial membrane potential, induced the accumulation of cells in G0/G1 phase, ending with apoptotic cell death. Pristimerin inhibited Akt and FoxO3a phosphorylation and induced nuclear accumulation of FoxO3a in UM‐1 cells, increased the expression of pro‐apoptotic proteins Bim、p27 Kip1, cleaved caspase‐3, PARP and Bax, and decreased the expression of Cyclin D1 and Bcl‐2. LY294002 or Akt‐siRNA inhibited the PI3K/Akt/FoxO3a pathway and promoted the Pristimerin‐induced apoptosis, while Pristimerin effects were partially abolished in FoxO3a knockdown UM‐1 cell cultures. Taken together, present results showed that Pristimerin induced apoptotic cell death through inhibition of PI3K/Akt/FoxO3a pathway in UM‐1 cells. These findings indicate that Pristimerin may be considered as a potential chemotherapeutic agent for patients with UM.